Association between individual-level and community-level socio-economic status and blood pressure among Inuit in Greenland. Issue 1 (1st January 2016) - Riva, Mylène; Larsen, Christina Viskum Lytken; Bjerregaard, Peter
Abstract : Background: Despite abundant evidence that socio-economic status (SES) is a fundamental determinant of health, there is a dearth of research examining association between SES, measured at the individual and community levels, and cardiovascular risk factors and morbidity among indigenous populations. Objectives: To examine the influence of individual-level and community-level SES on systolic and diastolic blood pressure among Greenlandic Inuit. Methods: Multilevel analysis of cross-sectional data from the Inuit Health in Transition – Greenland Survey, to which 3, 108 Greenlandic Inuit aged 18 years and older participated. Blood pressure is measured using an automatic device, according to standardized protocol. Individual SES is measured by education. Community socio-economic conditions are measured using combined information on average disposable household income and settlement type. Results: Education was not significantly associated with blood pressure. There was an inverse U-shape association between community socio-economic conditions and blood pressure with significantly lower SBP and DBP among participants living in remote traditional villages characterized by lower average disposable household income and in affluent more urbanized towns. Sex-stratified analyses demonstrate the salience of community conditions for men. Conclusions: The association observed between blood pressure and community-level socio-economic conditions suggests that public health and social policies, programmes and interventions aiming to improve living conditions might improve cardiovascular health in Greenland. Studies are required to further examine social gradients in cardiovascular risk factors and morbidity among indigenous populations using different measures of SES.